Integrasi Spiritualitas dan Pengembangan Diri melalui Pendidikan Keagamaan Katolik: Studi Kasus Mahasiswa STIPAR Ende dalam Mempersiapkan SDM Transformatif - Ina Wai, Florentina (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2025)
Catholic religious education in Catholic Higher Education Institutions (PTAK) plays a strategic role in shaping transformative human resources (HR) amid contemporary challenges. The background of this study arises from the need for HR who are not only intellectually competent but also possess spiritual depth, moral integrity, and a service-oriented mindset. The purpose of this research is to examine how Catholic religious education integrates spirituality and personal development in the formation process of students. Using a qualitative-descriptive approach, data were collected through observation, interviews, and documentation studies at Sekolah Tinggi Pastoral Atma Reksa Ende. The findings reveal that Catholic religious education, when contextualized and grounded in Gospel values, is capable of shaping students’ character to be reflective, ethical, and service-ready. The integration of spirituality into the curriculum and campus life strengthens intrinsic motivation, work ethic, and transformative leadership. The conclusion of this study affirms that Catholic religious education makes a significant contribution to the formation of holistic and transformative human resources. The implication is that formation strategies in PTAK must continue to be developed holistically in order to meet the ongoing needs of the Church, society, and the nation.